Community structure of zooplankton in Plawangan Timur Segara Anakan Cilacap - Agusfiana, Ega Dwi; Siregar, Asrul Sahri; Hidayati, Nuning Vita; Rukayah, Siti (Generasi Biologi Indonesia, 2022)
Plawangan Timur, located in the Segara Anakan Lagoon, Cilacap, is an estuary with many rivers flowing into it, and has a free connection with the open seas. Plawangan Timur waters suffer increased environmental pressures caused by anthropogenic activities, resulting in pollution, degradation of water bodies, and ecological changes. Ecological changes related to the physical and chemical estuary environment have been considered as major drivers of significant fluctuations in the zooplankton community structure. In order to manage and mitigate the effects of these changes, a prediction of their potential impacts on zooplankton communities is needed. This study aimed to determine the zooplankton community, which includes the abundance index, diversity index, evenness index and dominance index. The method used is a survey method with purposive random sampling at five stations. The F test and the Lackey Drop Microtransect Counting method were used to determine the abundance of zooplankton. The results showed that the abundance of zooplankton ranged from 113-598 ind/L (low); zooplankton diversity index ranged from 1.83-2.03 (medium); zooplankton evenness index ranged from 0.79-0.85 (high) and zooplankton dominance index ranged from 0.166-0.211 (low). Based on PP RI Number 22/2021, the physico-chemical factors of the Plawangan Timur waters are still at the safe concentration for zooplankton, except for the brightness, turbidity, Total Suspended Solid (TSS) and salinity.